Assessment of multiple climate change effects on plantation forests in New Zealand. (3rd August 2018) - Watt, Michael S; Kirschbaum, Miko U F; Moore, John R; Pearce, H Grant; Bulman, Lindsay S; Brockerhoff, Eckehard G; Melia, Nathanael
Abstract: Determining the magnitude of climate change effects is crucial for informing national economic strategies, forest management and offsetting increasing carbon emissions. This study synthesizes predicted climate change impacts and future biosecurity threats to New Zealand's plantation forests. Projected productivity increases for radiata pine ( Pinus radiata D. Don), the main commercial forest species in New Zealand, are slight due to changing climatic conditions. However including photosynthetic effects from increasing CO2, productivity gains across New Zealand averaged 19 per cent by 2040 and 37 per cent by 2090. This increased productivity results in marked increases in wind risk due to trees becoming taller and more slender. The average season length with 'very high and extreme' climatic fire risk increases by 71 per cent up to 2040 and by 83 per cent up to 2090. Currently, the most significant biotic disturbances in New Zealand plantations come from two needle cast diseases, for which climate projections show slight increases or decreases depending on the disease and region. Although insect pests currently cause little damage to New Zealand plantations, damage may increase in the future with projected increases in population and host susceptibility. It has not been possible to fully account for the effects of any new introductions of pests and pathogens and evidence from other countries with a significant resource of planted forests suggest this should not be underestimated. Potentially invasive weedy and damaging tree species are likely to expand their range under climate change and compete more strongly with plantations.